2020
DOI: 10.1021/acsanm.0c00327
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Dynamics Analysis of Nanoindentation of Graphene Nanomeshes: Implications for 2D Mechanical Metamaterials

Abstract: We report results of a comprehensive computational study of the mechanical response to nanoindentation of graphene nanomeshes (GNMs) or nanoporous graphene, namely, single-layer graphene sheets with periodic arrangements of nanopores, based on molecular-dynamics simulations of nanoindentation tests according to a reliable interatomic bond-order potential. We find the GNMs’ response to indentation to be nonlinearly elastic until fracture initiation, with elastic properties that depend strongly on the GNM porosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Figure c shows the force–displacement curves for the four superstructures that have exhibited the most pronounced inelastic responses; these superstructures have the lowest f sp 3 values among all the IB-TBG superstructures examined. As opposed to the smooth F (δ) curves generated in the nanondentation simulations of graphene nanomeshes, four force–displacement curves in Figure c, corresponding to f sp 3 values of 1.18%, 1.65%, 2.46%, and 4.05%, exhibit noticeable kinks that imply a nonlinear inelastic response. In these superstructures, each nanodiamond cluster formed between the two graphene layers consists of only three interlayer bonds, which is the smallest nanodiamond cluster that can be created for this type of commensurate bilayer graphene structures.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Figure c shows the force–displacement curves for the four superstructures that have exhibited the most pronounced inelastic responses; these superstructures have the lowest f sp 3 values among all the IB-TBG superstructures examined. As opposed to the smooth F (δ) curves generated in the nanondentation simulations of graphene nanomeshes, four force–displacement curves in Figure c, corresponding to f sp 3 values of 1.18%, 1.65%, 2.46%, and 4.05%, exhibit noticeable kinks that imply a nonlinear inelastic response. In these superstructures, each nanodiamond cluster formed between the two graphene layers consists of only three interlayer bonds, which is the smallest nanodiamond cluster that can be created for this type of commensurate bilayer graphene structures.…”
Section: Resultsmentioning
confidence: 78%
“…In the simulations, the cutoff distance of the Lennard-Jones part of the AIREBO potential is equal to 10.2 Å and the C−C cutoff distance is set to 2.0 Å to avoid unrealistically high stresses to develop in the sample at high deflections. 21,36,60 A similar setup to that in the study of nanoindentation of graphene nanomeshes 61 has been employed in this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The local mode force constants can quickly be calculated after a routine frequency calculation and therefore, can provide important guidance for the synthesis of a compound with a C−C bond of a particular strength. Work is in progress to investigate long CC bonds in nanotubes and crystals under pressure at ambient temperature [ 139 , 140 , 141 , 142 , 143 ].…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…Due to influence of preparation conditions, the graphene is also subject to structural defects, which can significantly alter its properties. [34][35][36][37] Based on computer simulations of nanoindentation, Chen et al [38] investigated the mechanical properties of graphene with different numbers of pores. Their results showed that the response of nanoporous graphene to indentation is non-linearly elastic and its elastic properties strongly depend on the porosity of nanoporous graphene.…”
Section: Introductionmentioning
confidence: 99%